Evaluation of the first Accelerated Bachelor of Science in Nursing program as a second career in Japan. - Saitoh, Aya; Shimoda, Kana; Kawabata, Ai; Oku, Hiromi; Horiuchi, Shigeko (Nurse Education Today, 2022)
The first Accelerated Bachelor of Science in Nursing (ABSN) program with a two-year educational period in Japan was developed in a nursing university in Tokyo in 2017 (i.e., 2017-ABSN two-year program or designated as program 1) for individuals aiming to pursue nursing as a second career. It replaced program 2, the second-year bachelor's degree transfer program which is a three-year program implemented from 1997 to 2016. The original and currently on-going four-year undergraduate Bachelor of Science in Nursing (BSN) is designated as program 3. To evaluate the 2017-ABSN two-year program from learners' perspective. We used a case-control study design. As cases, the subjects were third-year bachelor's degree transfer students of program 1 at the nursing university in Tokyo. As controls, second-year bachelor's degree transfer students of program 2 and four-year undergraduate students of program 3 in the same university were given a questionnaire when they graduated. The survey items were grouped into five scales: (1) The education you are receiving , (2) Studying nursing , (3) Stress level , (4) The highest score on the national nursing examination practice test , and (5) The vocational commitment. The mean score of each item was calculated and comparisons were conducted using the Mann Whitney test. Responses from 77 students (program 1), 23 students (program 2), and 133 students (program 3) were analyzed. The program 1 students had a significantly lower mean score on (1) The education you are receiving item " There is time for preparation and review " (p = 0.01). The program 1 students had a significantly lower score on (2) The studying nursing item " I can get the job (role) I want " (p = 0.01). The program 1 students had a significantly higher score on (4) The best score in the national nursing examination practice test (p = 0.01). Shortening the academic period to two years in program 1 had no effect on the knowledge base of the students. However, the program 1 students had a significantly lower score in their identity as a nurse. It is often difficult to acquire a new nursing culture in a short period from a previous culture that has already been mastered. Educators need to fully understand the characteristics of learners and provide them with individualized and professional guidance to further improve their skills. • There was no significant difference in stress scores between ABSN and other students. • ABSN students had significantly higher National Nursing Examination mock test score. • The ABSN students had a significantly lower score of identity development as a nurse.